PERSEPSI PESERTA DIDIK TENTANG KEGIATAN PENGEMBANGAN DIRI BIMBINGAN KONSELING DI KELAS VIII SMP NEGERI 20 PADANG - Nelfayanti, Nelfayanti; Kasih, Fitria; Nita, Rahma Wira (Bimbingan dan Konseling, 2013)
Â Counseling service in the school is the effort to help the students in to optimalize the development their self. SMP Negeri 20 Padang is one of the school that have done the students self development, but in fact the result of observation to some of the students found that many problems, such as the material is not effective and do not interesting for the students. The purpose of this research is to know the students perception about self development counceling in class VIII SMP Negeri 20 Padang. This is the descriptive research. The population is the students class VIII in SMP Negeri 20 Padang that registered in 2011/2012 that consist of eight class. The number of student 268. The sample is taken by simple random sampling technique. So the number of student is 59 from VIII.2 and VIII.6. the data is collect by using the arrangement of likert scala then analize by persentage tehnique. The group of the data are: very good, good, good enough and not good. From the reseach, it is found that 50,85% is good. The researcher suggest to the student to be more active and the teacher have to in crease the interaction with the student and give more chance to students.